Effectiveness of a physiotherapist-led triage and treatment service on WAITing time for adults with musculoskeletal pain referred to Australian public hospital physiotherapy clinics: a protocol for the WAIT-less trial - Ian A Harris; Andrew Lawson; Bethan Richards; Chris G Maher; Laurent Billot; David Roberts; Chris Needs; David Anderson; Nadine E Foster; Danielle Coombs; Marnee McKay; Joshua R Zadro; et al. (BMJ Open)
Introduction Musculoskeletal pain is the second leading cause of disease burden in Australia, and there is a need to investigate new models of care to cope with the increasing demand for health services. This paper describes the protocol for a randomised controlled trial investigating whether a physiotherapist-led triage and treatment service is non-inferior for improving function at 6 months and superior for reducing treatment waiting times, compared with usual care for patients with musculoskeletal pain referred to public hospital outpatient physiotherapy clinics.Methods and analysis A total of 368 participants (184 per arm) will be recruited from six public hospitals located in metropolitan Sydney, Australia. We will recruit adult patients newly referred to a public hospital physiotherapy outpatient clinic with a musculoskeletal condition that is typically managed by a physiotherapist (eg, back or neck pain, osteoarthritis, rehabilitation postorthopaedic surgery and sporting injuries). Participants will be randomised 1:1 to the physiotherapist-led triage and treatment service or usual care. A physiotherapist will telephone participants in the intervention group and match them to different modes and types of care based on baseline characteristics. Participants at low risk of poor outcomes (assessed by the Keele STarT MSK tool) will be given simple advice and education during this call and instructed to call back if their symptoms do not improve in 6 weeks. Participants at medium risk of poor outcomes or requiring postoperative rehabilitation will be offered a course of telehealth (videoconference) physiotherapy targeting exercise-based self-management. Participants at high risk of poor outcomes and/or with potential nonprogressive radiculopathy will be offered a course of usual clinic-based physiotherapy as per all participants in the usual care group. Physical function (Patient Specific Functional Scale) at 6 months postrandomisation and waiting time (time from randomisation to first treatment) are coprimary outcomes. Secondary outcomes include other patient outcomes (eg, pain), health resource use, adverse events, process measures (eg, adherence) and costs.Ethics and dissemination This trial has approval from the Sydney Local Health District Human Research Ethics Committee (RPAH Zone; X24-0090 and 2024/ETH00585). Recruitment will commence in September 2024 and is expected to be completed by December 2025 with follow-ups completed by December 2026. The results of the trial will be submitted for publication in reputable international journals and presented at relevant national and international conferences.Trial registration number ANZCTR (ACTRN12624000947505).